Особливості поліфонічного співіснування голосів-ідеологій у біблійній літературі - Біляшевич, Р. (Питання літературознавства, 2009)
Застосовується концепція літературної поліфонії М. Бахтіна до вивчення біблійних текстів. У першій частині статті розглядаються особливості поліфонічного поєднання традицій про царя Саула та царя Давида у Книгах Самуїла та Хронік. Друга частина містить аналіз засобів полеміки, що розгорнулася між Книгою Рут і Книгами Ездри та Неемії з приводу ставлення до чужинців. У розвідці велике значення надається вивченню ролі монотеїстичного світогляду у формуванні літературного методу Біблії. The article focuses on the approach to the biblical texts, which is based on M. Bakhtin’s conception of polyphony. The literary polyphony understood as the coexistence of different voices-ideologies (world-views) offers the new advantages to the interpretation of the polyform nature of the Bible. The first part of the article contains the analysis of the reconciliation of two conflicting traditions about Saul and David in the Books of Samuel and the Books of Chronicles. The second part of the article examines inner biblical dispute between two tendencies – the exclusion of the other (the Books of Ezra and Nehemiah) and the toleration of the stranger (the Book of Ruth). By means of “idyllic rereading” (I. Pardes) of different biblical books, the Book of Ruth claims that the rivalry and conflict are not necessary features in relations between biblical characters.